Evaluation of the Cervical Physiotherapeutic Treatment Needs, Work Ergonomics, and Necessity for Physical Activity Among Students of Dentistry at a Medical University. A Pilot Study - Kuć, Joanna; Żendzian-Piotrowska, Małgorzata (Frontiers in Psychology, 2020)
Introduction: A lot of general dental practitioners suffer from job-related health problems. They are more prone to numerous different physical and psycho-emotional triggers that aggravate their working conditions. The aim: The aim of the study was to evaluate cervical physiotherapeutic treatment needs, daily ergonomic habits and the necessity for physical activity among students of dentistry at a medical university. Material and methods: 112 generally healthy dentistry students (73 women, 39 men) were enrolled for the study. The age range was 20–32, with an average of 22.88 ± 2.7. The study included subjects in their second to fifth year of studies. The survey was conducted with respect to the questionnaires about possible physiotherapeutic treatments, physical activities, imaging tests and diagnoses as well as statements regarding the respondents’ knowledge and ergonomics habits. To estimate the association between the risk factor and neck disability as well as chronic pain, the Neck Disability Index, Perceived Stress Scale and the Graded Chronic Pain Scale were additionally applied. Results: 35.71% of dentistry students had undergo physiotherapy in the preceding year. 26.79% of the respondents declared that they underwent rehabilitation on a regular basis. The most common reasons for treatment were complaints of the cervical (7.14%), lumbar (3.57%) and thoracic spine (1.79%) as well as a combination of these symptoms. 6.25% of the subjects had started rehabilitation due to muscle relaxation. 34.82% of the study participants did not do any physical activity. Females exercised more often than males (p=0.02; 1-β= 0.65). Therapeutic exercises contributed to the improvement of well-being of 56% of students. 64.29% of the respondents chose a sitting position during pre-clinical and clinical classes and 26.79% of the subjects worked in sitting and standing postures. Conclusion: 26.79% of dentistry students required periodic therapeutic rehabilitation. 34.82% of the respondents were advised to implement systematic physical activity. Due to professional conditions, dental students are exposed to an early cervical spine disorders. The main factor influencing an early onset of such dysfunctions is increased stress level. An average level of pro-health awareness may be the reason for elevated cost of rehabilitation among this group of patients.